Access and quality of parks and associations with obesity: A cross-sectional study. (December 2017) - Hobbs, M.; Green, Mark A.; Griffiths, C.; Jordan, H.; Saunders, J.; Grimmer, H.; McKenna, J.
Abstract: Public health is increasingly engaging with multi-faceted obesity prevention efforts. Although parks represent key community assets for broader public health, they may not be distributed equitably and associations with obesity are equivocal. We investigated park access and quality relative to deprivation and obesity with individual-level data from the Yorkshire Health Study. Compared to the least deprived areas, the moderately and most deprived areas had a greater park access and park quality in terms of features and amenities. However, parks in the moderately and most deprived areas also had the most safety concerns and incivilities. Although deprivation was associated with obesity, contrary to current policy guidance, both park access and quality appear less important for understanding variations in obesity within this study. Although sub-group analyses by deprivation tertile revealed that low quality park amenities in highly and moderately deprived areas may be important for understanding obesity prevalence, all other associations were non-significant. Highlights: We investigated park access and quality relative to deprivation and obesity. Moderately and highly deprived areas had a greater park access and quality in terms of features and amenities. Moderately and highly deprived areas also had the most safety concerns and incivilities. There was no relationship between park access and park quality and obesity.